Theoretical Investigations on Electronic Structure, Structural Phase Stability and Optical Properties of Strontium Double Perovskites: Sr2AMoO6 (A=Mg, Zn). (2016) - Rameshe, B.; Gnanapoongothai, T.; Shanmugapriya, K.; Murugan, R.; Palanivel, B.
Abstract: Theoretical calculations are performed to investigate the electronic structure, structural phase stability and optical properties of double perovskite oxide semiconductors namely Sr2 AMoO6 (A= Mg, Zn) in tetragonal symmetry using WIEN2k. In order to estimate the ground state parameters, total energies are calculated with respect to molecular volume and the energies are fitted with Brich – Murnaghan equation of state. The estimated ground state parameters are comparable with the available experimental data. The band structure calculations for these compounds reveal that these compounds exhibit semiconducting behaviour with an indirect band gap. To explore the optical transitions in these compounds, the real and imaginary parts of the dielectric function are analyzed at ambient conditions and the important optical constants are calculated.